Analisis Pengalaman Mahasiswa Baru Universitas Islam Negeri Sumatera Utaran Dalam Menyesuaikan Diri Di Lingkungan Kampus - Ainul Mardiyah; Fadhila Habibi; Nabila Khairani; Juniar Rahmadani (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Adjustment is a crucial process that new students must undergo when entering college. The transition from a school environment to a university environment requires students to adapt to a more independent learning pattern, higher academic demands, and more diverse social dynamics. At UINSU, this adaptation process is unique because students face not only academic situations but also the religious culture that characterizes the campus. This study aims to describe the experiences of new students in adjusting to the university environment, identify factors that support and hinder adaptation, and explore the strategies used by students during this process. This study used a qualitative approach using interviews with several new UINSU students. The results indicate that the students' adjustment process is influenced by social relationships, the academic system, the campus environment, facilities, and internal psychological factors. Furthermore, social support from peers and campus activities play a significant role in helping students navigate the transition. These findings are expected to provide input for the university in providing adaptation support programs for new students to ensure a more comfortable and effective learning process.